The relationship between the big five personality traits and job satisfaction with virtual teaching among teachers of students with learning difficulties - Jawzaa Hamoud Almutairi; Abeer T Ahmed (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Job satisfaction has been described to be an important for individuals as well as for the society in general. However, several factors were introduced to be crucial for job satisfaction; one of the more influenced factors in satisfaction experiences is individual personality. The present study aim is to identify the relationship between the five major traits of personality and job satisfaction with virtual education among teachers of students with learning difficulties. MATERIALS AND METHODS: The research is a descriptive quantitative design. The research population consists of 94 male and female teachers who are involved in primary and intermediate public schools in Saudi Arabia. Data were then exposed to the analysis, namely, descriptive statistics, Pearson correlation, and Mann-Whitney U test to obtain the answers to the research questions at the level of <0.05. RESULTS: Based on the results, the most common personality trait among the study sample is conscientiousness, while neuroticism was the least common among the five traits. It was also found that there are differences between males and females in all dimensions of job satisfaction with virtual education (satisfaction with the nature of work - the relationship with colleagues and bosses - the relationship with parents) and the overall score in favor of females, except for the dimension of the relationship with colleagues and superiors, where males and females are equal. CONCLUSION: The average score of the personality types and job satisfaction is moderate. Job satisfaction has a significant relationship with personality types. In addition, partial significant differences were found among the study variables. Given the importance of identifying teachers' personality in the workplace, reducing psychological and work factors effects in the educational environment among teachers can be helpful to enhance their job satisfaction. The study therefor, enumerated implications and recommendations based on the findings.